Sustainable Organic Waste Reduction Using Black Soldier Fly Larvae: The Effect of Music Variation on Bioconversion Performance - Dhea Andini; Bimastyaji Surya Ramadan; Sri Sumiyati (Jurnal Penelitian Pendidikan IPA, 2026)
Black Soldier Fly (BSF) larvae are widely recognized as a sustainable solution for organic waste reduction due to their ability to convert waste into valuable biomass. This study aimed to evaluate the effect of music variations on the bioconversion performance of BSF larvae. A laboratory experiment was conducted using five sound treatments: no music (A), random music (B), dangdut music (C), classical music (D), and metal music (E). The larvae were fed organic waste, and the observed parameters included Waste Reduction Index (WRI), Efficiency of Conversion of Digested Feed (ECD), Survival Rate (SR), and protein content. The results showed that music variations did not significantly affect all observed parameters (p > 0.05). However, the classical music treatment tended to produce higher WRI and ECD values compared to the other treatments. The survival rate and protein content of the larvae were relatively similar across all treatments. These findings indicate that sound exposure does not significantly affect the bioconversion performance of BSF larvae, but certain types of music may provide more favorable conditions. This study supports the application of BSF larvae in sustainable organic waste management.